The impact of HLA class I and EBV latency‐II antigen‐specific CD8+ T cells on the pathogenesis of EBV+ Hodgkin lymphoma. (13th November 2015) - Jones, K.; Wockner, L.; Brennan, R. M.; Keane, C.; Chattopadhyay, P. K.; Roederer, M.; Price, D. A.; Cole, D. K.; Hassan, B.; Beck, K.; Gottlieb, D.; Ritchie, D. S.; et al.
Summary: In 40% of cases of classical Hodgkin lymphoma (cHL), Epstein–Barr virus (EBV) latency‐II antigens [EBV nuclear antigen 1 (EBNA1)/latent membrane protein (LMP)1/LMP2A] are present (EBV + cHL) in the malignant cells and antigen presentation is intact. Previous studies have shown consistently that HLA‐A*02 is protective in EBV + cHL, yet its role in disease pathogenesis is unknown. To explore the basis for this observation, gene expression was assessed in 33 cHL nodes. Interestingly, CD8 and LMP2A expression were correlated strongly and, for a given LMP2A level, CD8 was elevated markedly in HLA‐A*02 – versus HLA‐A*02 + EBV + cHL patients, suggesting that LMP2A‐specific CD8 + T cell anti‐tumoral immunity may be relatively ineffective in HLA‐A*02 – EBV + cHL. To ascertain the impact of HLA class I on EBV latency antigen‐specific immunodominance, we used a stepwise functional T cell approach. In newly diagnosed EBV + cHL, the magnitude of ex‐vivo LMP1/2A‐specific CD8 + T cell responses was elevated in HLA‐A*02 + patients. Furthermore, in a controlled in‐vitro assay, LMP2A‐specific CD8 + T cells from healthy HLA‐A*02 heterozygotes expanded to a greater extent with HLA‐A*02‐restricted compared to non‐HLA‐A*02‐restricted cell lines. In an extensive analysis of HLA class I‐restricted immunity, immunodominant EBNA3A/3B/3C‐specific CD8 + T cell responses were stimulated by numerous HLA class I molecules, whereas the subdominant LMP1/2A‐specific responses were confined largely to HLA‐A*02. Our results demonstrate that HLA‐A*02 mediates a modest, but none the less stronger, EBV‐specific CD8 + T cell response than non‐HLA‐A*02 alleles, an effect confined to EBV latency‐II antigens. Thus, the protective effect of HLA‐A*02 against EBV + cHL is not a surrogate association, but reflects the impact of HLA class I on EBV latency‐II antigen‐specific CD8 + T cell hierarchies.